The effects of growth opportunities between different type of institutional investors and corporate risk-taking in Malaysia - Hanis Hazwani, Ahmad (2020)
Global financial crises and technological transition have forced the managers to adopt revolutionary methodologies by taking risky investments. However, excessive risk-taking may harm firms. Agency Theory suggested that misalignment incentives between the shareholders and the managers contributed to the crisis. Institutional investors had been utilized in previous studies due to their diversification capacities. However, empirical studies on the heterogeneous of institutional investors is limited. This study aims to explore the effect of growth opportunities between various forms of institutional investors and corporate risk-taking. The panel data for 518 Malaysian non-financial firms, from 2000 to 2018 period, were analyzed using Ordinary Least Squared (OLS), Generalized Least Squared (GLS), and Generalized Moments of Method (GMM). Return on Asset (ROA), Stock Return, as well as Total Debt to Total Asset (TDTA) and Total Debt to Total Capital (TDTC), were used as risk-taking proxies to explain the corporate risk-taking behaviour while Market to Book Ratio (MTB) and Tobin’s Q was utilized as growth opportunities proxies. The proportion of the different types of institutional investors was employed in this study, which classified as the proportion of total institutional ownership in firms, institutional ownership by top five, institutional ownership by largest, active institutional investors, passive institutional investors, long-term ownership, and short-term ownership. Results revealed that heterogeneous of institutional investors have a significant impact on corporate risk-taking. However, not all types of institutional investors could mitigate unnecessary risk-taking such as passive institutional investors and short-term ownership. On the other hand, growth opportunities provided by the interaction between different types of institutional investors and corporate risk-taking have significant influences in high and low-growth firms. This study, therefore, recommended that the regulators and policymakers should carefully review the Malaysian Code for Institutional Investors (MCII) to update governance code by providing appropriate incentives for different types of institutional investors that strengthen the corporate governance system in Malaysia